Integrasi Konsep Visa Tinggal Terbatas Dan Izin Tinggal Terbatas Dalam Pengembangan Teknologi Berkelanjutan: Studi Perspektif Inovasi Digital - Rayhan, Daffi Aditya; Puspitasari, Fadhila; Melia, Cindy Arfa; Simbolon, Andre; Nabila, Aprilia Asya An (Jurnal Sains dan Teknologi (JSIT), 2025)
In Indonesia's immigration system, the Limited Stay Visa (VITAS) and Limited Stay Permit (ITAS) are two main instruments that are interrelated. However, so far there are gaps in the system that cause less than optimal synchronization between VITAS and ITAS. Problems that often arise include data duplication, long bureaucratic processes, and limited interoperability between related institutions' systems. This research aims to analyze the integration between Limited Stay Visa (VITAS) and Limited Stay Permit (ITAS) in the development of sustainable immigration technology in Indonesia, especially from the perspective of digital innovation. The research approach uses a qualitative method with literature study and policy analysis to examine regulations, digital systems, and service practices related to VITAS and ITAS. The results show that the integration of e-Visa and ITAS Online electronic systems can significantly improve the efficiency, transparency, and speed of immigration services. This digital transformation also contributes to reducing paper usage and cutting bureaucracy, which is in line with sustainability principles. However, there are still challenges related to technological infrastructure, digital literacy of officers, and technical constraints that need to be addressed to ensure optimal implementation. This research recommends strengthening human resource capacity, improving IT infrastructure, and public education as strategic steps going forward. The digital integration of VITAS and ITAS is an important foundation in building a modern, inclusive, and sustainable immigration system.